2023
DOI: 10.3389/fpubh.2023.990051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic benzene poisoning on aberrant mitochondrial DNA methylation: A prospective observational study

Abstract: Benzene is used as an industrial solvent, which may result in chronic benzene poisoning (CBP). Several studies suggested that CBP was associated with mitochondrial epigenetic regulation. This study aimed to explore the potential relation between CBP and mitochondrial DNA (mtDNA) methylation. This prospective observational study enrolled CBP patients admitted to Shenzhen Prevention and Treatment Center for Occupational Diseases hospital and healthy individuals between 2018 and 2021. The white blood cell (WBC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Formerly reviewed [10] publications that investigated effects of benzo The majority of new human in vivo studies focus on gene-specific methylation, the identification of potential biomarkers for early detection of benzene toxicity, and the influence of benzene on DNA methyltransferase expression. For example, peripheral blood cells derived from benzene-exposed workers demonstrated hypomethylation of STAT3, which was significantly correlated with oxidative stress variables [81], and MT-COI a gene associated with oxidative phosphorylation [82]; these epigenetic modifications represent potential predictive marks for benzene exposures. Also, it was found that low-level occupational benzene exposure was associated with hypermethylation of tumor suppressor genes p15 INK4b [83], p14ARF, and p16 INK4A [84]; aberrant methylation of p16 INK4A was significantly correlated with genomic instability caused by benzene-induced chromosomal abnormalities.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Formerly reviewed [10] publications that investigated effects of benzo The majority of new human in vivo studies focus on gene-specific methylation, the identification of potential biomarkers for early detection of benzene toxicity, and the influence of benzene on DNA methyltransferase expression. For example, peripheral blood cells derived from benzene-exposed workers demonstrated hypomethylation of STAT3, which was significantly correlated with oxidative stress variables [81], and MT-COI a gene associated with oxidative phosphorylation [82]; these epigenetic modifications represent potential predictive marks for benzene exposures. Also, it was found that low-level occupational benzene exposure was associated with hypermethylation of tumor suppressor genes p15 INK4b [83], p14ARF, and p16 INK4A [84]; aberrant methylation of p16 INK4A was significantly correlated with genomic instability caused by benzene-induced chromosomal abnormalities.…”
Section: Non-coding Rnasmentioning
confidence: 99%